Peningkatan Layanan Publik Pemerintah Desa Asemgede Melalui Pendampingan Perakitan Running Text - Hariono, Tholib; Widya, Moh Anshori Aris; Yaqin, Nurul; Ashoumi, Hilyah; Aliuddin, Mohammad Alex; Al Fahhiz, Mohammad Hufaif Ibri; Tuzzahroh, Lutfiyah (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2024)
The assistance program for developing running text in Asemgede Village, Ngusikan Subdistrict, Jombang Regency, aims to enhance the understanding and skills of village officials in designing, assembling, and operating running text technology. This technology is designed as an appropriate solution to improve the fast, efficient, and modern dissemination of information, which is highly needed by the village community. Using the Participatory Action Research (PAR) method, this activity actively involves village officials in the learning process. Evaluation results show a significant increase in participants' understanding of running text after the socialization. Additionally, the use of running text provides economic and social benefits by reducing information dissemination costs and increasing community participation. This program contributes to the village's digital literacy and encourages local innovation in public services.